Механізація вирощування вівса з удосконаленням сівалки СЗ-3,6А - Попов, Артем Володимирович; Popov, Artem (ЦНТУ, 2025)
У кваліфікаційній роботі проаналізовано механізовані процеси вирощування вівса. Виявлено недоліки процесу сівби, запропоновано новий широкозахватний посівний агрегат, який має вищу продуктивність, менші питомі витрати палива та створить максимально сприятливі умови для розвитку рослин. Представлена вдосконалена конструкція однодискового сошника з ущільнюючим кілем, що дозволить значно підвищити якість загортання насіння. Розроблені рекомендації з охорони праці покращать умови роботи механізатора. The qualification work analyzed the mechanized processes of oat cultivation. The shortcomings of the sowing process were identified, and a new wide-sweeping sowing unit was proposed, which has higher productivity, lower specific fuel consumption, and will create the most favorable conditions for plant development. An improved design of a single-disk coulter with a sealing keel has been presented, which will significantly improve the quality of seed wrapping. The developed recommendations on labor protection will improve the working conditions of the machine operator.
Oat cultivation mechanization with improved SZ-3,6A seeder
Keywords: овес; технологічна карта; широкозахватний агрегат; сівба; сошник; oats; technological map; wide-grip unit; sowing; coulter